2019
DOI: 10.4103/jpbs.jpbs_229_18
|View full text |Cite
|
Sign up to set email alerts
|

A comparative evaluation of the effectiveness of chitosan-based dressing and conventional method of hemostasis in patients on oral antithrombotic therapy without therapy interruption

Abstract: Aims and Objectives: To assess the effectiveness of chitosan-based dressing after extraction in individuals on antithrombotics, without modification of their treatment schedule. Materials and Methods: A randomized comparative study was carried out on 40 subjects who had two extraction sites, in dissimilar quadrants. The surgical site was chosen at random and post-extraction hemostasis was achieved by a custom-cut chitosan dressing (study site) and sterile cotton gauze d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 12 publications
1
14
0
Order By: Relevance
“…Again, the efficacy of this material was compared to the use of cotton gauze dressings. Not only was the mean time for hemostasis significantly reduced with chitosan-based dressings, but the incidence of adverse events-dry socket and pus discharge-was also notably lower [169]. The combination of fibrin glue and chitosan dressings has also been explored to improve the hemostatic process in patients with hemophilia.…”
Section: Hemostasismentioning
confidence: 99%
“…Again, the efficacy of this material was compared to the use of cotton gauze dressings. Not only was the mean time for hemostasis significantly reduced with chitosan-based dressings, but the incidence of adverse events-dry socket and pus discharge-was also notably lower [169]. The combination of fibrin glue and chitosan dressings has also been explored to improve the hemostatic process in patients with hemophilia.…”
Section: Hemostasismentioning
confidence: 99%
“…In a case series of 35 patients on antiplatelet agents or anticoagulants who failed initial management with cautery and nasal packing, 32 patients were successfully treated with application of a foam anterior pack wrapped in a chitosan sheet [20]. A small study of 40 patients on oral anticoagulation undergoing multiple tooth extractions compared a site treated with a chitosan pledget with a site treated with gauze and pressure and found decreased bleeding times and decreased postoperative pain in the chitosan treated site [21]. Another small study of 20 patients on oral anticoagulants undergoing dental extraction of multiple teeth found that the extraction sites treated with chitosan had shorter bleeding times than control extraction sites treated with a collagen matrix plug [22].…”
Section: Chitosan (Hemconmentioning
confidence: 99%
“…And the most widely used scaffolding agents are modified collagen, oxidized regenerated cellulose (ORC), absorbable gelatin, and chitosan dressing. [ 12 14 ]…”
Section: Introductionmentioning
confidence: 99%